Desenvolvimento de um dispositivo mecânico para acentuação da ação muscular excêntrica em equipamentos de musculação com sistema de camos - Marcel Bahia Lanza (2011)
Several studies have shown that the human being is able to produce highest values of strength during eccentric muscle action than during concentric and isometric muscle action. But most of the equipment traditionally used in resistance training, which have a mechanical function characterized by a system of cables and pulleys, has the limitation of not being able to control the mechanical load imposed on the individual differently during the performance of different actions muscle, i.e. the mechanical load is the same during different muscle actions. Thus, a mechanical device capable of modulating the load during the eccentric muscle action can bring great benefit to bodybuilders and can allow a prescription for physical training more suited to athletes who seek a maximum increase of muscular strength. Thus, the purpose of this study is divided into two stages: a) the development of a mechanical device which, adapted to a traditional equipment, enables increasing the mechanical load imposed on the eccentric action and allow graduating this increase in mechanical load according with the desired intensity, b) verify the effect of using the device to a mechanical load 40% higher during the eccentric action in relation to concentric muscle during activation of biceps femoris and medial gastrocnemius using surface electromyography, for the knee flexion. The synergistic muscle movement (medial gastrocnemius) showed no significant differences of integral EMG (iEMG) between sets of protocols analyzed. In contrast, the agonist muscle movement (biceps femoris) showed significant differences in iEMG between sets when compared Protocol A series with Protocol B. It is concluded that the new device achieved the objective to regulate the intensity of effort during the eccentric action and still shows positive results in muscle activation.